Favourable outcomes for childhood acute lymphoblastic leukaemia in an isolated setting: The Tasmanian experience. Issue 2 (4th June 2018) - Heath, John A.; Macdonald, Molly; Starosta, Helen; Hitchins, Samuel; Wills, Karen; Daubenton, John D.
Abstract: Background: Tasmania is a large, relatively isolated island located south of mainland Australia with limited tertiary level paediatric oncology services. Aims: To benchmark regional outcomes for childhood acute lymphoblastic leukaemia (ALL) against published international standards. Methods: We undertook a retrospective cohort study, analysing the clinical characteristics and health outcomes of all children diagnosed with and treated for ALL in Tasmania, Australia between 2006 and 2015. Results: Thirty‐five patients aged less than 18 years were diagnosed with ALL in the study's 10‐year period. Twenty‐eight cases were precursor B cell in origin, with 7 cases of T‐cell ALL. The great majority of children (30/35; 86%) received their entire first line treatment in Tasmania. Major treatment‐related toxicities, including allergic drug reactions, and episodes of acute pancreatitis, deep venous thrombosis and bacterial sepsis, were managed locally, with one death secondary to overwhelming infection and multiorgan failure. The overall and event‐free survival rates for childhood ALL were 30/35 (86%) and 28/35 (80%), respectively. Conclusions: These results compare favourably with published results from large international cooperative group trials based in developed countries. Continued local treatment with appropriate support from a dedicated specialist paediatric oncology unit is therefore justified.